Overcoming challenges in refining the current generation of coronary stents. (2nd November 2021) - Mori, Masayuki; Sakamoto, Atsushi; Sato, Yu; Kawakami, Rika; Kawai, Kenji; Cornelissen, Anne; Abebe, Biniyam; Ghosh, Saikat; Romero, Maria E.; Kolodgie, Frank D.; Virmani, Renu; Finn, Aloke V.
ABSTRACT: Introduction: Late stent thrombosis caused by delayed vascular healing and prolonged local inflammation were major drawbacks of 1 st generation drug-eluting stents (DES). Strut design, biocompatibility of polymer, and drug-release profiles were improved in 2 nd and 3rdgeneration DES. Accordingly, the indications for percutaneous coronary intervention with DES have been expanded to more complex patients and lesions. Despite these improvements, significant barriers such as greater flexibility in the duration of dual-antiplatelet therapy (DAPT) as well as reducing long-term stent-related events remain. To achieve ideal short- and long-term results, these existing limitations need to be overcome. Areas covered: We will discuss the current limitations of coronary DES and how they might be overcome from pathological and clinical viewpoints. Expert opinion: Optimizing DAPT duration after stent implantation and prevention of in-stent neoatherosclerosis are two major issues in current DES. Overcoming these drawbacks is a prerequisite toward achieving better short- and long-term clinical outcomes. New technologies including platform design, polymer types, and anti-proliferative agent itself might lead to further improvements. Although the initial experience with bioresorbable scaffold/stents (BRS) was disappointing, positive results of clinical studies regarding novel BRS are raising expectations. Overall, further device innovation is desired for overcoming the limitations of current DES.